The process of validating public information systems framework - Iza Azura Ahmad Bahar; Syed Nasirin Syed Zainol Abidin; Esmadi Abu Abu Sema; Tamrin Amboala; Suddin Lada; Hadzariah Ismail; Nona Masnie Mohd. Nistah (Springer, Cham, 2021)
This paper presents the process of creating and validating public sector information systems (PSIS) development framework. Three development methodologies were put together to increase the validity of the proposed framework, i.e., 1) methodologies for data gathering, 2) procedures for framework development and 3) methodologies for validating the framework created. Exploratory investigations with UK local councils were organised, reflecting several approaches to PSIS development. Based on the findings, a PSIS development framework is presented.